The public budgeting and finance primer key concepts in fiscal choice - Ryu, Jay Eungha (M.E. Sharpe, 2014)
This book succinctly summarizes key theoretical concepts in fiscal choice of public budgeting and finance. It explains key concepts in fiscal choice ultimately from the perspective of a choice between politics and economics in completely stand-alone chapters for each concept.